Revolusi Pembelajaran di Pesantren Modern: Pengaruh dan Implikasi Pembelajaran Bersanad - Ansori, Muhammad Zainul; Fattah, Abdul; Nasri , Ulyan; Muhtar, Fathurrahman (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyze the impact of changes in the sanad-based learning approach in modern Islamic boarding schools on students, teachers, and the schools themselves. Additionally, this research aims to investigate whether this approach provides a positive contribution to the understanding of religion, character development, and the relevance of Islamic boarding schools in contemporary society. The research method used is a literature review with a qualitative approach. Data were obtained from relevant literature sources, including scholarly journals, books, articles, and documents related to sanad-based modern Islamic boarding school education. Data analysis was conducted using a content analysis approach to identify common patterns in the accessed literature. The results of the literature review indicate that the sanad-based learning revolution has a positive impact on students' understanding of religion. Furthermore, this approach also has the potential to assist in shaping students' character by emphasizing ethical and moral values. Islamic boarding schools that implement this approach also tend to be more relevant in contemporary society, attracting student interest and gaining broader support from the community. In conclusion, based on the results of this literature review, it can be concluded that the revolution in sanad-based learning in modern Islamic boarding schools has a positive influence on enhancing religious understanding, character development, and the relevance of these schools in society. This approach has helped Islamic boarding schools remain relevant in the face of modern challenges. The contribution of this study is to provide a better understanding of the changes in the approach to learning in modern Islamic boarding schools and its positive contribution to Islamic education in Indonesia. This study can serve as a foundation for further development in the field of Islamic boarding school education and sanad-based learning.